Scleroderma. A case presentation. - Rubén Bembibre Taboada; Annia Alvarado Borges; Niurka Galende Hernández; Julio Cortizo Hernández (Medisur)
This article presents a brief review about generalized sclerosis (sclerodermia ) and reports a case with such disease talking into consideration that the patient received clinical intensive care assistaance and had a clinical diagnosis supoported by lab test for a clinical and differential diagnosis. Medical treatment was applied for the disease and for the possible complications, but the patients follow up was wrong due to multi organ failure as a consequence of derlying disease.